A Systematic Literature Review of Digital Media in Enhancing Arabic Listening Comprehension - Yonan Yonan; Nanang Kosim; Ade Arip Ardiansyah (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STAI DR. KHEZ. Muttaqien Purwakarta, 2026)
This study aims to map the use of digital media in enhancing Arabic listening skills and to identify research limitations in related studies published over the last five years (2022–2026). The study employed a Systematic Literature Review (SLR) method following the PRISMA guidelines to ensure a systematic and transparent process of literature selection and synthesis. Data were collected from three databases, namely Garuda, DOAJ, and ERIC. A total of 150 articles were initially identified, of which 13 met the inclusion criteria. The findings indicate that digital media used in Arabic listening instruction can be classified into four categories: audio-based media, audio visual media, Mobile-Assisted Language Learning (MALL), and Learning Management Systems (LMS). The review further reveals that audio visual media and MALL based applications demonstrate more consistent effectiveness in improving listening skills due to their integration of multimodal elements, interactivity, and structured feedback. However, the reviewed studies still exhibit several methodological limitations, including small sample sizes, short intervention periods, and research designs that lack sufficient rigor. Therefore, future studies should develop experimental designs, conduct longitudinal investigations, and perform comparative analyzes across different media types to strengthen the empirical evidence supporting technology enhanced Arabic listening pedagogy.